How did athletes train and avoid injuries during the COVID-19 quarantine period? - Al Attar, W. S. A.; Husain, M. A. (Trends in Sport Sciences, 2021)
Introduction. During the isolation period of COVID-19, athletes may not train, which leads to an increased risk of injury, which can be slight or more severe depending on their fitness level. Aim of Study. The current study aimed to investigate training exercises and injury prevention programs during the COVID-19 quarantine period among athletes. Material and Methods. A self-administered web-based survey was developed. The survey aimed to obtain information concerning exercises and injury prevention protocols implemented by athletes during the COVID-19 quarantine period. The survey`s other goal was to investigate the type of exercises such as running, strength, stretching, plyometrics, balance, or injury prevention programs and the average training time. Data was collected in the period between April to June 2020. Results. A total of 606 respondents completed the survey, with a response rate of 80% from 132 countries worldwide. Most respondents were male (n = 353, 58.3%), and aged between 30 to 39 years (n = 175, 28.9%). Sixty-one percent of the total sample reported that they had been training during the quarantine period. They consisted of amateur-level (n = 180, 29.7%) and semi-professional athletes (n = 159, 26.2%). Squat, push up, single-leg squat, and side lunges were the top five implemented exercises with an average training time of 30 to 60 minutes. Most injury prevention protocols (18.8%) were reported as non-specified programs, followed by the Knee Injury Prevention Program (KIPP) (12.5%) and the iSPRINT Injury Prevention Program (10.6%). Conclusions. Most athletes continued their training and exercise during the COVID quarantine period to maintain their physical fitness level and reduce injury levels once they resume their regular training.